Measuring Fabric Moisture Content with Improved Wheatstone Bridge (Journal of Fiber Bioengineering and Informatics, 2014)
Use of improved Wheatstone bridge in measurement of fabric moisture content as well as its measurementprinciple is introduced in this paper. A new detection circuit of fabric moisture content based on improvedWheatstone bridge is designed, and its measurement result is standardized by oven method. The fittedcurves representing fabric moisture content of different materials are plotted after the experimental datais processed. Compared with oven method, errors are analyzed. The results reveal that the detectioncircuit can accurately measure the changes in fabric moisture content and errors are small (within 1%for cotton), which can meet the need of fabric moisture content detection online system.
Keywords: Moisture Content; Improved Wheatstone Bridge; Detection Online; Fabric Resistance